Acute and chronic effects of the benzodiazepine receptor ligand FG 7142: proconvulsant properties and kindling. - Little, H. J. (Nature Publishing Group, 1984)
The effects of the acute and chronic administration of the beta-carboline benzodiazepine receptor ligand, FG 7142 were studied in mice. On acute administration FG 7142 (at doses between 10 and 40 mg kg-1) lowered seizure thresholds to infused pentylenetetrazol (PTZ) but showed an unusual dose-response curve in that higher doses had less effect. The duration of action was considerably longer than that of other beta-carbolines, such as ethyl-beta-carboline-3-carboxylate (beta CCE). During repeated administration, doses of FG 7142 which were initially proconvulsant subsequently produced generalized seizures on average in 60% of animals after 12 once daily treatments. This seemed to be a form of chemical kindling. The effects of different drug administration regimes were studied. Once daily dosage was shown to be the optimum for kindling production, and was therefore used for subsequent experiments. Kindling lasted for at least one month after 12 single once daily doses of 40 mg kg-1 (FG 7142). The administration of the benzodiazepine antagonist Ro 15-1788 concurrent with FG 7142 prevented kindling. When Ro 15-1788 was given to kindled animals along with a challenge dose of FG 7142, it prevented the expression of kindled seizures. These data show that kindling is mediated via the benzodiazepine receptor.